2021
DOI: 10.3390/jcm11010202
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Salvage Radical Prostatectomy from Open to Robotic and Further to Retzius Sparing Surgery

Abstract: Salvage radical prostatectomy (sRP) has evolved from open to minimally invasive approaches. sRP can be offered to patients with local recurrence to improve biochemical recurrence (BCR)-free and overall survival. We evaluate oncological outcome and continence after retropubic (RRP), conventional (cRARP), and Retzius-sparing robotic (rsRARP) surgery. Materials/methods: A total of 53 patients undergoing sRP between 2010 and 2020 were included. Follow-up included oncological outcome and continence. Results: sRP wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…These values were taken on biopsy after initial treatment. Schuetz et al [ 20 ] reported initial GG prior to index treatment, thus, these were not included. In terms of initial treatments, patients most frequently underwent external beam radiation therapy (EBRT) in both groups (52% vs. 49%).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These values were taken on biopsy after initial treatment. Schuetz et al [ 20 ] reported initial GG prior to index treatment, thus, these were not included. In terms of initial treatments, patients most frequently underwent external beam radiation therapy (EBRT) in both groups (52% vs. 49%).…”
Section: Resultsmentioning
confidence: 99%
“…Cryoablation was not common with 2% of SRS and 13% of SS patients choosing this modality. Other treatments were quite rare (4% vs. 2%), with the most common being C-12 ion ablation, used exclusively in the Schuetz et al [ 20 ] series. There were no significant differences between initial treatments in any study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations